Comparative analysis of biomechanical characteristics between the new Tai Chi elastic band exercise for opening and closing movement and elastic band resistance training for the reverse fly movement - Liu, Mingyu; Ren, Mengyao; Zhang, Peng (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details